Theory of Media Literacy : a Cognitive Approach. - Potter, Dr. W. James (SAGE Publications, 2004)
Theory of Media Literacy: A Cognitive Approach comprehensively explains how we absorb the flood of information in our media-saturated society and examines how we often construct faulty meanings from those messages. In this book, author W. James Potter enlightens readers on the tasks of information processing. By building on a foundation of principles about how humans think, Theory of Media Literacy examines decisions about filtering messages, standard schema to match meaning, and higher level skills to construct meaning.